The Managerial Skills of Principal and Academic Supervision on Teacher’s Performance - Amril, Amril; Ahyani, Nur; Rahman, Andi (Journal of Social Work and Science Education, 2023)
Head of madrasa should have managerial abilities since these skills help to concentrate the process of coordinating instruction. To promote the improvement of a madrasa head’s administrative abilities, the supervisor arranges academic supervision on a continuous basis in an effort to improve educational quality by improving teacher’s performance in executing their professionally. The purpose of this study was to demonstrate the impact of the madrasa principal’s administrative abilities and academic supervision held by the supervisor on teacher’s performance. As a result, the research was conducted utilizing a quantitative descriptive technique. According to the findings of this study, the madrasa principal’s administrative abilities have an influence on teacher’s performance in partial testing. Similarly, academic supervision provided by the madrasah supervisor had a good and substantial impact on teacher’s performance in partial testing. Concurrently, the factors of management abilities and academic supervision have a favorable and substantial influence on the performance of Madrasah Aliyah instructors in Lempuing District, hence confirming the alternative hypothesis in this study.